Cardiopulmonary considerations for high school student-athletes during the COVID-19 pandemic: NFHS-AMSSM guidance statement - Drezner, J. A.; Heinz, W. M.; Asif, I. M.; Batten, C. G.; Fields, K. B.; Raukar, N. P.; Valentine, V. D.; Walter, K. D. (Sports Health: A Multidisciplinary Approach, 2020)
SARS-CoV-2, the novel coronavirus that causes COVID-19 illness, presents unique health issues that should be considered in student-athletes prior to a return to sports and exercise. While the vast majority of young persons afflicted with the coronavirus have mild symptoms or remain asymptomatic, the infection can cause direct injury or inflammation to the heart and lungs, especially in patients ill enough to require hospitalization. Cardiopulmonary concerns from COVID-19 arise from data in severely ill adult patients, where approximately 1 in 5 hospitalized patients suffers from cardiac or thromboembolic (clotting) complications.9,13 However, evidence on the prevalence and risks of these complications in adolescents and in individuals who have had a milder form of the illness remains limited.7